Enzymatic Amide Tailoring Promotes Retro‐Aldol Amino Acid Conversion To Form the Antifungal Agent Aspirochlorine. Issue 43 (24th September 2018) - Tsunematsu, Yuta; Maeda, Naoya; Yokoyama, Mamoru; Chankhamjon, Pranatchareeya; Watanabe, Kenji; Scherlach, Kirstin; Hertweck, Christian
Abstract: Aspirochlorine is an unusual antifungal cyclopeptide produced by Aspergillus oryzae, an important mold used for food fermentation. Whereas its structure suggested that a non‐ribosomal peptide synthetase assembles the cyclopeptide from phenylalanine and glycine building blocks, labeling studies indicated that one Phe moiety is transformed into Gly after peptide formation. By means of genetic engineering, heterologous expression, biotransformations, and in vitro assays, we dissected and reconstituted four crucial steps in aspirochlorine biosynthesis, which involve two cytochrome P450 monooxygenases, (AclL and AclO), a methyltransferase (AclU), and a halogenase (AclH). We found that the installation of the N‐methoxylation of the peptide bond sets the stage for a retro‐aldol reaction that leads to the Phe‐to‐Gly conversion. The substrate scopes of the dedicated enzymes as well as bioassays revealed that the peptide editing has evolved to optimize the antifungal action of the natural product. Abstract : Editing the peptide : Dissection and reconstitution of aspirochlorine biosynthesis in vivo and in vitro revealed that sequential amide N‐methoxylation sets the stage for the retro‐aldol cleavage of a phenylalanine building block into a glycine residue. This unprecedented amino acid conversion in a peptide plays an essential role in the evolution of this potent antifungal agent.